(untitled) (Eurasian Journal of Ecology, 2021)
Soybeans as a high-protein and oilseed crop are recognized as strategically important in the world ranking of agricultural crops. Global soya bean production is in constant dynamic development. An increase in the area under this crop is occurring in all countries, including Kazakhstan. The average yield of soybeans in Kazakhstan is 21.5 c / ha. The increase in crop yields is due not only to the development of new high-yielding varieties, but also to the application of modern agro-technological approaches and the treatment of seeds and vegetative plants with growth stimulants. The paper presents the results of research on the effect of treatment of soybean seeds of different ripeness groups with a nitrogen-fixing preparation Histick and trace elements – Co, Mo. Seed pre-treatment revealed varietal responsiveness to the application of stimulants. None of the preparations had a positive effect on the yield of the ultra-ripe variety Ivushka. The yield of the early maturing variety Birlik KV increased significantly by 2.1 c/ha when seeds were co-treated with the nitrogen-fixing preparation Histick and trace elements Mo+Co. In the mid-late variety Zhansaya and the late-ripening variety Lastochka a significant increase in yield was noted only when the seeds were treated with nitrogen-fixing agent Histick by 1.6 and 2.1 c/ha, respectively. Key words:soybean, micronutrients, productivity traits, yield.